Revealing disparities in representation in knowledge generation and guideline development - Carlos P. B. Almeida; Afom T. Andom; Alain Casseus; Jacquelyn-My Do; Alain Gelin; Leonid Lecca; Maxo Luma; Michael Mazzi; Carole D. Mitnick; Jean Claude Mugunga; Melino Ndayizigiye; Natalie Nguyen; et al. (BMC Health Services Research)
Abstract Background Multidrug-resistant tuberculosis (MDR/RR-TB) is a major global health challenge, disproportionately affecting low- and lower-middle-income countries (LLMICs). The World Health Organization (WHO) generates guidance to address the problem. Here, we explore the extent to which guidance and related knowledge are generated by experts living in the most-affected countries and consider the results in the context of the movement to decolonize global health. Methods We examined the composition of World Health Organization (WHO) MDR/RR-TB treatment Guideline Development Groups (GDGs) from 2016 to 2022. We classified GDG members according to the MDR/RR-TB burden and World Bank income level of the country of their institutional affiliation. We also searched PubMed to identify peer-reviewed publications from 2016 to 2023 which emanated from individual-patient-data meta-analysis like those done for Guideline review, and classified the publication authors according to the same indicators. Results There were 33 high-burden MDR/RR-TB countries during the time period. Of these, 72.1% were LLMICs and none was high-income. In contrast, only 30.3% of WHO GDG members and 10.4% of peer-reviewed publication authors were from LLMICs. Representatives from high-MDR/RR-TB-burden countries comprised 34.3% of WHO GDG members and 14.7% of authors of guideline-related publications. Conclusions The important imbalance between the geographical distribution of lived experience with MDR/RR-TB and the distribution of individuals generating knowledge and guidance on treatment of MDR/RR-TB can have clinical and resource implications. Countries may reject or defer guideline adoption because of a mismatch between that guidance and local disease epidemiology. Funding conditioned on compliance with guidelines can exacerbate health inequalities. The movement to decolonize global health considers representation disparities as epistemic injustice, that is unfair treatment in the process of generating, sharing, or receiving knowledge. Reform is possible in many of the institutions involved in generation of global health knowledge, such as: meaningful participation of LLMICs in projects as a requirement for research funding, improved attention to the epistemic and geographical location of journal editorial staff, and broader inclusion in guidelines committees. Better alignment of participation in knowledge generation with burden of disease holds potential for reducing inequality and improving relevance of guidance for the lived experience with MDR/RR-TB.